Steroids differentially inhibit the nicotinic acetylcholine receptor - Garbus, Ingrid (2001)
The effect of various natural and synthetic steroids on the function of the nicotinic acetylcholine receptor (AChR) was studied at the single-channel level. AChR channel kinetics was affected by some substitutions in the cyclopentaneperhydrophenantrene ring. Functionally relevant substitutions shortened channel open state duration, an effect that varied for different steroids. The presence of a polar group at C11 contributed to the inhibitory potency of the steroid. Among mono-hydroxy- lated steroids such as 11- and 17-OH progesterone, the highest potency was displayed by the former showing a level similar to that of the reference compound, hydrocortisone. When the effects were analyzed in terms of the octanol–water partition coefficient, a linear relationship was unexpectedly found between the hydrophilicity of the steroids and their inhibitory potency.